(untitled) (Scientific journal of the Fergana State University, 2024)
Historical written sources are of great importance in elucidating the history of the Sevinchhojakhan family. Effective use of them is a deep study of the history of this period, reconstruction of the full picture of political, socio-economic events, correct analysis of the causes and consequences of their origin, socio-economic and cultural aspects of the period. helps to brighten up your life. There are many historical sources about the historical events that took place in the regions of Central Asia in the 16th century. They contain valuable information about the history of the period of Sevinchhojakhan, which we are studying. Historical sources and scientific literature were used to study the researched topic. Historical sources were critically approached based on the degree of relevance of their authors to the narrated events and their personal views. The method of comparative analysis was used in the process of logically connecting the information in the sources. Based on the development of historical events and phenomena in interregional relations, scientific hypotheses were expressed. We found it necessary to analyze the historical sources used in the article by groups based on their characteristics and pay attention to their particularly important aspects for this research.